Bài 4: Tìm nghiệm của các đa thức sau đây: a) Q(x)= 4x – 2(3x – 5)+ 2 b) P(x)= $x^{2}$ – 7x + 12 23/07/2021 Bởi Melody Bài 4: Tìm nghiệm của các đa thức sau đây: a) Q(x)= 4x – 2(3x – 5)+ 2 b) P(x)= $x^{2}$ – 7x + 12
Bài 4 a) 4x-2(3x-5)+2=0 4x-6x+10+2=0 -2x=-12 x=6 b) x²-7x+12=0 x²-(6x+x)+(9+3)=0 (x²-6x+9)+(3-x)=0 (3-x)²+(3-x)=0 (3-x)(3-x+1)=0 ⇒\(\left[ \begin{array}{l}3-x=0 => x=3 \\3-x+1=0 => x=4\end{array} \right.\) Vậy S={ 3 ; 4 } Bình luận
Đáp án + Giải thích các bước giải: `a//` Cho đa thức `Q(x)=0` `->4x-2(3x-5)+2=0` `->4x-6x+10+2=0` `->-2x+12=0` `->-2x=-12` `->x=6` Vậy nghiệm đa thức `Q(x)` là : `x=6` `b//` Cho đa thức `P(x)=0` `->x^{2}-7x+12=0` `->(x^{2}-4x)-(3x-12)=0` `->x(x-4)-3(x-4)=0` `->(x-4)(x-3)=0` `->` \(\left[ \begin{array}{l}x-4=0\\x-3=0\end{array} \right.\) `->` \(\left[ \begin{array}{l}x=4\\x=3\end{array} \right.\) Vậy nghiệm đa thức `P(x)` là : `x=4;x=3` Bình luận
Bài 4
a) 4x-2(3x-5)+2=0
4x-6x+10+2=0
-2x=-12
x=6
b) x²-7x+12=0
x²-(6x+x)+(9+3)=0
(x²-6x+9)+(3-x)=0
(3-x)²+(3-x)=0
(3-x)(3-x+1)=0
⇒\(\left[ \begin{array}{l}3-x=0 => x=3 \\3-x+1=0 => x=4\end{array} \right.\)
Vậy S={ 3 ; 4 }
Đáp án + Giải thích các bước giải:
`a//`
Cho đa thức `Q(x)=0`
`->4x-2(3x-5)+2=0`
`->4x-6x+10+2=0`
`->-2x+12=0`
`->-2x=-12`
`->x=6`
Vậy nghiệm đa thức `Q(x)` là : `x=6`
`b//`
Cho đa thức `P(x)=0`
`->x^{2}-7x+12=0`
`->(x^{2}-4x)-(3x-12)=0`
`->x(x-4)-3(x-4)=0`
`->(x-4)(x-3)=0`
`->` \(\left[ \begin{array}{l}x-4=0\\x-3=0\end{array} \right.\)
`->` \(\left[ \begin{array}{l}x=4\\x=3\end{array} \right.\)
Vậy nghiệm đa thức `P(x)` là : `x=4;x=3`